The effectiveness of an enrichment teaching program based on STEM approach in developing the 21st skills of intermediates school students - Almutairi, Nasser Mohammed (Journal of Educational and Psychological Sciences, 2023)
The current research aimed to identify the effectiveness of an enrichment teaching program based on the integrated educational (STEM) approach in developing the twenty-first century skills of middle school students in Jeddah Governorate. The research sample consisted of (60) students in the third intermediate grade in the General Administration of Education in Jeddah Governorate in the academic year 1444 AH. The semi-experimental approach based on pre-post measurement for one group was relied upon. According to the experimental design of the research, the research experiment was applied to the research sample for four consecutive months. The data were collected through Google form and after that the results were monitored and analyzed statistically. The results showed the effectiveness of the enrichment teaching program based on the STEM educational approach in developing the twenty-first century skills of middle school students. The study recommended a number of recommendations, the most important of which is the employment of the STEM educational approach in enhancing 21st Century skills at students.